ANALYSIS OF THE PERFORMANCE OF THE AMPHIBIOUS CESSNA 172 SP - Maruli Tua Sagala, Josep; Suyatmo, Suyatmo; Irfansyah, Ade (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Amphibious aircraft are aircraft with the ability to take off and land on water, other than on the runway like airplanes in general. This type of aircraft will be one of the transportation options to reach islands throughout Indonesia. Performance is a term used to describe the ability of an aircraft to meet certain limitations that make it useful for a particular purpose. The subject of aircraft performance includes speed, altitude, range and fuel efficiency, required take-off distance, rate of climb and also aircraft control speed. The purpose of this study was to analyze the factors that affect performance on the Cessna 172 SP amphibious aircraft based on weight, analyze the factors that can normalize the performance of the Cessna 172 SP amphibious aircraft to be normal, and analyze the takeoff performance and landing performance on the Cessna 172 SP type amphibious aircraft. The research method used in this research uses the method of observation and literature study, with the stages of data collection followed by processing to get the results of the research analysis. The research results obtained in the study of factors that affect the decrease in the performance of the aircraft are the addition of float which has a weight of 212 kg. The results of the takeoff performance analysis based on the weight of the additional float is that the empty weight of the aircraft has increased from 767 kg to 979 kg, thus affecting the ground roll during takeoff which was originally 931 ft to 1,012 ft. The results of the landing performance analysis based on the weight of the added float is that the empty weight of the aircraft has increased, which was originally 767 kg to 979 kg, thus affecting the landing distance during landing which was originally 605 ft to 612 ft.